Accountability and transparency: Is this possible in hospital governance? - Patience Aseweh Abor; Carlos Kokuvi Tetteh (Cogent Business & Management, 2023)
Health institutions in developing countries need to be transparent and accountable to attain universal health coverage and effective institutions as mandated by Sustainable Development Goals (SDG) 3 (target 3.8) and SDG 16 (target 16.6), respectively. This study seeks to achieve two objectives: 1) to examine financial, performance, and political or democratic accountability at the teaching hospitals in Ghana toward achieving good hospital governance; 2) to examine event and process transparency practices in the teaching hospitals. A comparative case methodology was employed with data from structured questionnaires administered to hospital administrators. The study revealed only one of the four teaching hospitals understudy is accountable in terms of financial, political/democratic, and performance accountability. Also, the same teaching hospital was found to practice both process and event transparency, establishing the correspondence between accountability and transparency. The study concludes that most of the teaching hospitals in Ghana have challenges with accountability and transparency at varying intensities. Thus, efforts to ensure accountability and transparency are recommended for quality healthcare delivery and good hospital governance.
Keywords: 650; accountability; Ghana; hospital governance; teaching hospital; transparency